Formação docente para o ensino superior: uma inovação em cursos de lato sensu - Gaeta, Maria Cecília Damas (2007)
This research aims at demonstrating that the lato sensu post graduation courses can become an option for the formation and development of university teachers. Today we observe a clear demand for the pedagogical background and an evident gap for related spaces towards this process, since the stricto sensu post graduation programs are mainly aimed at the development of research and researchers. From the principles of the action-research in a qualitative approach, it does an initial theoretical-reflective data gathering encompassing the fields of integrated curriculum, teaching knowledge and tourism. Later, the investigation on creation, implementation, evaluation and reformulation of a Teacher development course in tourism and related areas has brought elements to answer to the problem posed. It concludes that this level of education can become an option for the development of university and college teachers, provided that they are base on a consistent and serious educational proposal, in a curriculum judiciously designed according to the principles of the subject area intended and with a properly qualified faculty